Lonely servitude : child domestic labor in Morocco - Becker, Jo ([New York, N.Y.] : Human Rights Watch, 2012)
"This 73-page report found that some child domestic workers- who are overwhelmingly girls - toil for 12 hours a day - 7 days a week, for as little as US$11 a month. Some girls told Human Rights Watch that their employers frequently beat and verbally abused them, denied them education, and sometimes refused them adequate food" - Publisher's website.
"In Morocco, thousands of children--predominantly girls--work in private homes as domestic workers. Known as petites bonnes, they are often recruited from poor rural areas to work for families in the cities, cooking and preparing meals, washing dishes, doing laundry, washing floors and carpets, shopping for groceries, and caring for young children. Despite Moroccan law prohibiting the employment of children under age 15, Human Rights Watch found that girls as young as eight work long hours for little pay as child domestic workers. Some work up to 12 hours a day, seven days a week, for as little as US$11 per month. Some girls told Human Rights Watch that their employers beat and verbally abused them, denied them education, or refused them adequate food. Isolated in private homes and far from their families, many have no idea where to turn for help. According to government statistics, Morocco has made significant progress in recent years in reducing overall rates of child labor and increasing the number of children who attend school. Rates of child domestic labor also appear to have declined. However, existing efforts are not sufficient to address the unique characteristics of child domestic labor. Labor inspectors lack authority to access private households in order to identify child domestic workers. Criminal prosecutions against employers responsible for physically abusing child domestic workers are rare, and fines almost never imposed on employers who hire under-age children for domestic work. Lonely Servitude recommends that the Moroccan government strictly enforce laws prohibiting child domestic labor below the age of 15, expand public awareness campaigns about child domestic labor, and create an effective system to identify and remove child domestic workers who are illegally employed or subject to abuse" - P. 4 of cover.
Summary. Under-age employment ; Deceptive intermediaries ; Abusive and exploitative working conditions ; Progress ; More action needed ; Key recommendations -- Methodology -- I. Child domestic work in Morocco. Characteristics of child domestic workers : age, origin, and schooling ; Reasons for working ; Recruitment into domestic work ; Other recruitment -- II. The life of a child domestic worker. Long hours and lack of rest ; Wage exploitation ; Verbal and physical violence ; Sexual violence and harassment ; Food deprivation and living conditions ; Isolation ; Lack of access to education ; Lack of protection and pressure to keep working positive experiences ; The future -- III. Legal framework. Moroccan law ; International law -- IV. Moroccan government efforts to address child domestic labor. Education ; Enforcement of the prohibition on child labor ; Assistance ; Public education, training, and support to NGOs ; Criminal prosecution -- V. Response by other actors. Non-governmental organizations ; International organizations : the ILO and UNICEF -- Conclusion -- Recommendations. To the Moroccan government ; To Morocco's parliament ; To the Ministry of Employment and Professional Training ; To the Ministry of Solidarity, Women, Family, and Social Development ; To the Ministry of Justice ; To the Ministry of National Education, Higher Education, Staff Development, and Scientific Research ; To international donors, including the United States, France, and Belgium ; To the International Labour Organization and United Nations Children's Fund (UNICEF) -- Acknowledgements -- Appendix I -- Appendix II.
"This report was researched and written by Jo Becker" - p. 56.
Includes bibliographical references.
Keywords: Trabalho Infantil; Marrocos; Direitos Humanos; Direitos da Criança